2011
DOI: 10.1186/1471-2164-12-264
|View full text |Cite
|
Sign up to set email alerts
|

Microarray analysis and scale-free gene networks identify candidate regulators in drought-stressed roots of loblolly pine (P. taeda L.)

Abstract: BackgroundGlobal transcriptional analysis of loblolly pine (Pinus taeda L.) is challenging due to limited molecular tools. PtGen2, a 26,496 feature cDNA microarray, was fabricated and used to assess drought-induced gene expression in loblolly pine propagule roots. Statistical analysis of differential expression and weighted gene correlation network analysis were used to identify drought-responsive genes and further characterize the molecular basis of drought tolerance in loblolly pine.ResultsMicroarrays were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
89
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(98 citation statements)
references
References 121 publications
7
89
2
Order By: Relevance
“…The plant's transcriptional changes during drought stress have been extensively studied in a wide range of species, including Arabidopsis (Seki et al, , 2002Kilian et al, 2007;Huang et al, 2008;Matsui et al, 2008), oilseed rape (Brassica napus) , rice (Oryza sativa) (Lenka et al, 2011;, maize (Luo et al, 2010;Chen et al, 2011), loblolly pine (Pinus taeda) (Lorenz et al, 2011), and banana (Musa spp) (Davey et al, 2009). Analyses of gene expression, transcriptional regulation, and signal transduction in plants subjected to drought treatments have revealed pathways involved in plant response to water stress Abe et al, 2003;Tran et al, 2004).…”
Section: Classical Approaches For Tackling Drought Stressmentioning
confidence: 99%
“…The plant's transcriptional changes during drought stress have been extensively studied in a wide range of species, including Arabidopsis (Seki et al, , 2002Kilian et al, 2007;Huang et al, 2008;Matsui et al, 2008), oilseed rape (Brassica napus) , rice (Oryza sativa) (Lenka et al, 2011;, maize (Luo et al, 2010;Chen et al, 2011), loblolly pine (Pinus taeda) (Lorenz et al, 2011), and banana (Musa spp) (Davey et al, 2009). Analyses of gene expression, transcriptional regulation, and signal transduction in plants subjected to drought treatments have revealed pathways involved in plant response to water stress Abe et al, 2003;Tran et al, 2004).…”
Section: Classical Approaches For Tackling Drought Stressmentioning
confidence: 99%
“…The first assay contained randomly chosen SNPs detected in silico from transcriptome sequence data and are expected to represent neutral variants (hereafter, control SNPs; see Chancerel et al 2013 for more details). Briefly, SNPs were identified from .600,000 sequences obtained from a set of 17 cDNA libraries of different tissues without any prior experimental treatment and were integrated into a unigene set previously used for linkage mapping (Chancerel et al 2013).The second OPA comprised 384 SNPs distributed in 221 candidate genes (Supporting Information, File S2; see also Budde et al 2014) that included drought-stress candidates identified in Mediterranean (P. pinaster and P. halepensis) and American (P. taeda) pines (Eveno et al 2008; Eckert et al 2010a,b;Grivet et al 2011) and genes overexpressed under abiotic stress (Lorenz et al 2011;Perdiguero et al 2013) and/or that have shown some evidence of adaptive value in different conifers (e.g., Eveno et al 2008; Eckert et al 2010a,b;Grivet et al 2011;Lepoittevin et al 2012;Mosca et al 2012). SNPs were selected after resequencing these genes in a discovery panel that covered the entire natural range of P. pinaster (see Chancerel et al 2011;Budde et al 2014).…”
mentioning
confidence: 99%
“…Herein, we performed the preselection of genes by pinpointing candidates from previous population and functional studies. These genes included drought-stress-response candidates detected by population genetics (e.g., Mosca et al 2012; see also or expression studies (Lorenz et al 2011;, as well as variants previously associated to wood properties, cold hardiness, and growth in maritime pine (Pot et al 2005;) and other conifers Eckert et al 2010a,b). Many of these genes belong to gene families that have been associated with adaptive responses in other plants.…”
Section: Discussionmentioning
confidence: 99%
“…The second OPA comprised 384 SNPs distributed in 221 candidate genes (Supporting Information, File S2; see also that included drought-stress candidates identified in Mediterranean (P. pinaster and P. halepensis) and American (P. taeda) pines Eckert et al 2010a,b; and genes overexpressed under abiotic stress (Lorenz et al 2011; and/or that have shown some evidence of adaptive value in different conifers (e.g., González-Martínez et al 2007Eckert et al 2010a,b;Mosca et al 2012). SNPs were selected after resequencing these genes in a discovery panel that covered the entire natural range of P. pinaster (see .…”
Section: Methodsmentioning
confidence: 99%